5q+9=-6

Simple and best practice solution for 5q+9=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5q+9=-6 equation:



5q+9=-6
We move all terms to the left:
5q+9-(-6)=0
We add all the numbers together, and all the variables
5q+15=0
We move all terms containing q to the left, all other terms to the right
5q=-15
q=-15/5
q=-3

See similar equations:

| 18+.05n=50.50 | | 5(4x-15x)+12=4x-2 | | q-67/8=3 | | 23-2h=3 | | 4n+9n=n-36 | | s/3+18=20 | | 19-13p=17p+5 | | 2(2m-16)=3(2m+4) | | 5a-27=-7 | | 12g=13g | | 6(w+15)=6 | | 7r=16=93 | | 22y=11(3+y | | 3x+9=6x+10 | | 2(6+4n)=12+8n | | j-82/3=4 | | -8-(-1t)=-9.9 | | -6x+9=4(5)-x | | 8-15g=15+8g | | k=7/7=3 | | 134+24+x=180 | | g-3+ -6=-7 | | P(-3p-5)=0 | | y=14=72 | | 48+53+x=180 | | d+12=39 | | X^2+8x+(128/9)=0 | | 3+2x10=70 | | 3-(x/8)=(-9/2) | | q+5/9=5/6 | | s-77/2=7 | | 2n(8+5n)-3=45 |

Equations solver categories